VERTICAL FARMING A HOPE FOR INDIA TO ERADICATE THE CRISIS OF FOOD SHORTAGE - Dr.Sumanta Bhattacharya; Dr Heera Lal; Bhavneet Kaur Sachdev (Galaxy International Interdisciplinary Research Journal, 2021)
Vertical farming is the new hope for tackling many of the issues across the globe from food shortage to climate change , environmental degradation to promotion of biodiversity . With the growing population , it is estimated that by 2050 , we will have no food left to serve the population , if we don’t increase our cultivation rate by 70 % in the upcoming years , Water crisis soil erosion and deforestation has made the land unfit for cultivation where vertical farming is a solution to this problem which produces plants with minimal water and no soil in a closed environment .Indoor farming is becoming relevant in many parts of urban sector and India since 2019 has been practicing vertical agriculture and it has ample amount of scope and also can overcome many issues from climate change to poverty and bring in fresh air and fresh organic food to the people , the problem of cold storage infrastructure and the problem of rotten food will also end , as indoor farming requires no particular climate condition , it is grown using LED light and artificial intelligence , with public awareness it can also help to eradicate poverty and double the production of food in India .